Development of a new LiDAR database management system using open source software - Ahmad Arshad, Khairil Izwan (2016)
LiDAR Survey is one alternative method that gives an extra advantage especially to get coordinate and height value data. It is known as the best way to retrieve coordinate and height data for the broad area in short period of time. Data produced from LiDAR is enormous but sadly, they are kept, not in proper relational database management system. They have been kept in Hard disk or Digital Versatile Disk (DVD) after serving their purpose. This way of storing make searching difficult because these data may come from different file versions and varieties of a coordinate system. Survey Department and Mapping (JUPEM) is the only government agency that has been given an authority to handle all airborne data based on Circular of Prime Minister Agency (JPM 1/2007). This researched been carried out to enhanced the way of LiDAR data been stored. Currently, management of these data is not so effective. Lots of time and money involved just to know the data availability and retrieves the data. The objective of this researched is to a developed database using open source software called LiDAR Database Management System (LiDMS). Next, the evaluation of LiDMS is based also on its performance via online. This system can work on windows, iPhone Operating System (iOS) and android which is used the MySQL as a database. User satisfying test has been carried out to see how the user accepts the LiDMS. The user experience evaluation test result showed that, LiDMS Portal able to be used by using Windows, smartphone, ios or others gadget platform smoothly but it is subject to bandwidth and speed of the processor used. Overall this researched manage to developed a portal that benefit to the government, researcher, decision maker, and client either to apply for a new fly permit via online, monitoring the permit given as follow Prime Minster Circular 1/2007, upload or retrieve the data or just to browse the data location availability in Malaysia.